Effect of Plant Growth Promoting Microbes on Bael (Aegle marmelos) Seedlings in Nursery - Verma, R. K.; Tripathee, Richa; Chourasiya, Sonam; Thakur, A. K. (Indian Forester, 2015)
Response of arbuscular mycorrhizal (AM) fungi and Azospirillum, was studied on growth and shoot Phosphorus contents of bael (Aegle marmelos) in nursery. Application of AM fungi in combination with Azospirillum produced maximum plant biomass, shoot phosphorus content and root colonization. Application of Azospirillum along with AM fungi showed a synergistic effect on root colonization and is being recommended to boost the growth of bael seedlings in nursery.